Acute response of some iron indices of young elite wrestlers to three types of aerobic, anaerobic, and wrestling exercise - Tayebi, S. M.; Mahmoudi, A. A. (Montenegrin Journal of Sports Science and Medicine, 2017)
The present study was conducted to investigate the acute responses of some iron indices of young elite wrestlers to three types of aerobic, anaerobic, and wrestling exercises. A total of 24 elite volunteer wrestlers were randomly categorized into three groups (n=8) aerobic, anaerobic, and routine wrestling exercises. The exercises were conducted during three non-consecutive sessions within one week. The aerobic exercises included 35 min of continuous running with 130 beats per minute (BPM) on a treadmill; the anaerobic exercises included 15 min circuit movements and 15 min rest with 160 BPM, and the wrestling training included routine wrestling exercises. Blood sampling was done in the first and third sessions in order to study the acute responses which included four stages of 1 h before, immediately, 3 h, and finally 24 h after exercises. The study of the acute response to the first session showed that the type of exercise had no effect on serum iron (p=0.57). Furthermore, the serum ferritin (p=0.012) and TIBC (p=0.006) affected was affected by type of exercise. The study of the acute response to the second session showed that the type of exercise had no effect on serum ferritin (p=0.731) and TIBC (p=0.231), rather the serum iron was affected by the type of exercise (p=0.01). Conclusively, the study of acute response showed that wrestling exercises led to a decline in iron stores during exercise and reduced total iron binding capacity during a 24-h recovery period. The study of acute exercise after a short adaptation period showed that despite the fact that serum iron had no change in anaerobic and wrestling exercises over the passage of time, it changed during aerobic exercise and 24-h recovery periods. Furthermore, the progress of iron deficiency was only observed in the first stage which prevented its progress to the next stage.